Surgical stage in the era of molecular profiling of endometrial cancer - Kasius J.C.; Kildal W.; Vrede S.W.; Askautrud H.A.; Pradhan M.; van Altena A.M.; Tobin K.-A.R.; Knoll K.; Reijnen C.; Reimann S.; Dackus G.; Vlatkovic L.; et al. (Pergamon Press, 2026)
Introduction Molecular classification has reshaped risk stratification in endometrial cancer (EC), yet the relevance of tumor spread within molecular subgroups has not been reported so far. Material and methods This multicenter retrospective study included 2056 EC patients treated between 1994 and 2018 across 11 European centers. All histopathological subtypes and FIGO stages were included. Tumors were classified into four molecular subgroups: POLE -mutated ( POLE mut), mismatch repair deficient (MMRd), no specific molecular profile (NSMP), and TP53/ p53 abnormal (p53abn). Clinical and pathological data were extracted from existing cohort databases. Results Patients were diagnosed with FIGO stage I (69 %), II (9 %), III (16 %), and IV (6 %), and classified into: POLE mut (8 %), MMRd (28 %), NSMP (44 %), and p53abn (21 %). The overall 5-year cancer-specific death (CSD) and recurrence rates were 16.5 % (95 % CI, 14.9 %-18.2 %) and 23.8 % (95 % CI, 22.0 %-25.7 %), respectively. In multivariable analysis cancer-specific survival (CSS) was independently associated with molecular subtype, FIGO stage, age, histopathological type, grade, lymphovascular space invasion, adjuvant therapy, residual tumor, and lymphadenectomy. FIGO stage was significantly associated with CSD also in within each molecular subgroup (p < 0.001). Patients with tumors confined to the uterus had the most favourable prognosis. Lymph node metastases significantly decreased CSS in POLE mut, MMRd, and p53abn groups. Within FIGO stage IV, molecular subtype was not significantly related to outcome. Discussion Surgical stage remains a strong prognostic factor across molecular subtypes and should be considered alongside molecular classification when tailoring adjuvant treatment in EC. © 2025 The Authors.